2015
DOI: 10.1016/j.sajb.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Frost, Portulacaria afra Jacq., and the boundary between the Albany Subtropical Thicket and Nama-Karoo biomes

Abstract: a b s t r a c t a r t i c l e i n f o Available online xxxx Edited by WJ BondNumerous shrublands exist in areas where soil moisture should support tree growth. In South Africa, the dwarf shrublands of the Nama-Karoo biome and tree-dominated vegetation of the Albany Subtropical Thicket biome share a boundary that is often abrupt. This boundary is not associated with edaphic or rainfall transitions. Field observations and leaf-level experiments suggest that the vulnerability of thicket species to frost damage is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…This amount of temperature buffering during frost can have large impacts for tropical plants because most tropical plants are vulnerable to temperatures of just a few degrees below freezing (Sakai & Larcher, 1987). Thus protective effect of trees against extreme cold has been recognized to be important for maintaining mangrove forests (Devaney et al, 2017;Osland et al, 2015), subtropical thicket (Duker, Cowling, Preez, & Potts, 2015), and tropical alpine forest (Rehm & Feeley, 2015) near the limit of their cold tolerance. In all these systems, damage to trees is greatest where tree cover is lowest, thereby reinforcing existing patterns of tree density.…”
Section: Discussionmentioning
confidence: 99%
“…This amount of temperature buffering during frost can have large impacts for tropical plants because most tropical plants are vulnerable to temperatures of just a few degrees below freezing (Sakai & Larcher, 1987). Thus protective effect of trees against extreme cold has been recognized to be important for maintaining mangrove forests (Devaney et al, 2017;Osland et al, 2015), subtropical thicket (Duker, Cowling, Preez, & Potts, 2015), and tropical alpine forest (Rehm & Feeley, 2015) near the limit of their cold tolerance. In all these systems, damage to trees is greatest where tree cover is lowest, thereby reinforcing existing patterns of tree density.…”
Section: Discussionmentioning
confidence: 99%
“…particle size, depth, infiltration rate, sodium and electrical conductivity) are consistent across the valley floors and shale-derived sections of the valley slopes (Becker et al, 2015). Nonetheless, Karoo shrubland replaces thicket on the valley floor-this is largely driven by frost (Duker et al, 2015a(Duker et al, , 2015b. In these valleys, some of the thicket-shrubland treelines are intact and clearly defined due to historically low levels of livestock pressure (Ian Ritchie, 2016, personal communication); this boundary has become blurred in places as livestock has removed thicket, and Karoo shrubland species have subsequently invaded.…”
Section: Cold Air Pooling Model Calibrationmentioning
confidence: 78%
“…These 'calibration valleys' are located in the Zuurberg mountain range in the north-eastern portion of the Cape Fold Mountains. Temperature loggers and field observations have confirmed that radiative frost (0 C at ground level) occured on valley floors up to 15 times each winter as a result of CAP on still and clear nights (detailed in Duker et al (2015aDuker et al ( , 2015b).…”
Section: Cold Air Pooling Model Calibrationmentioning
confidence: 81%
See 1 more Smart Citation
“…rock agama, dwarf chameleons, and cicadas; Price et al 2007;Swart et al 2009;Tolley et al 2006). The lower temperatures, both globally (Zachos et al 2001) and regionally (Holmgren et al 2003;Talma & Vogel 1992), coupled with the frost sensitivity observed in many of the thicket's component species (Duker et al 2015a;Duker et al 2015b) is suggested to have driven thicket vegetation into fragmented refugia (Cowling et al 2005), as reflected by Nymania capensis.…”
Section: Glacial Refugia: Pleistocene Climatic Cycles As Drivers Of Dmentioning
confidence: 98%